Green initiative: Building sustainable organic rice agribusiness in Malang Raya - Ariadi Bambang Yudi; Relawati Rahayu (BIO Web of Conferences)
This study highlights the importance of sustainability in the organic rice agribusiness of Malang Raya, which has significant potential due to its fertile land but faces challenges such as high production costs, limited market access, and insufficient knowledge about organic practices among farmers. The research aims to identify and analyze these key issues and develop effective sustainable organic rice agribusiness strategies. Utilizing a qualitative approach, the study involves in-depth interviews and surveys with farmers, agribusiness entrepreneurs, and organic agriculture experts, along with a SWOT analysis (Strengths, Weaknesses, Opportunities, Threats) to provide a thorough assessment. Findings reveal that limited access to information and organic farming technologies, combined with suboptimal government and institutional support, are major problems. However, the substantial market potential and strong consumer interest in organic products present significant growth opportunities. The study underscores the need for enhanced collaboration between government, research institutions, and farming communities to strengthen the organic rice agribusiness ecosystem. Recommendations include intensive farmer training, improved market access through partnerships with e-commerce and supermarkets, and strengthened regulations supporting organic farming.